Pengaruh Lingkungan Belajar Berdasarkan Teori Belajar Behaviorisme Terhadap Motivasi Belajar IPS Siswa - Aisyah Nur Sayidatun Nisa; Yutasak Lamoonsuk; Moh. Sholeh (Contemporary Education Review, 2025)
SMPN 7 Semarang City is one of the educational institutions that has a relatively conducive learning environment, both in terms of cleanliness, classroom comfort, and harmonious social relations between school residents. However, behind these supportive environmental conditions, the learning motivation of eighth grade students in Social Studies (IPS) is still relatively low. This phenomenon is the basis for conducting research to analyze the extent to which the learning environment influences student learning motivation by linking it to behaviorism learning theory. This study uses a quantitative approach with a survey method of 68 respondents selected through simple random sampling techniques from a total population of 210 students. Data were collected through observation, questionnaires, and interviews, then analyzed using simple linear regression with the help of SPSS software version 26. The results of the analysis show that the learning environment has a significant influence on student learning motivation, as evidenced by a significance value of 0.000 (<0.05) and a calculated t value of 5.264 (> t table 1.667). These findings indicate that the better the quality of the learning environment, both in terms of physical and social aspects, as well as family support, the higher the students' motivation in participating in social studies learning. Improving the quality of the learning environment aligns with the principles of behaviorism, which states that the development of positive learning behaviors can be achieved through the provision of appropriate stimuli and reinforcement. Efforts to create a supportive learning environment are a strategic step in increasing motivation and optimal student learning outcomes.